Teaching at university a guide for postgraduates and researchers - Morss, Kate (SAGE, 2005)
Offers you with the basic skills required to enter those first lectures, tutorials, lab-sessions and assessments with confidence. This book offers: advice; portfolio sections at the end of chapter; an emphasis on helping you to get started and build up your confidence; and, integration of theory (in small doses) with practice.